The Comparison of Plasma Cortisol Levels between 0.125% Bupivacaine and 5 mg Continuous Oxycodone in Lower Extremity Orthopedic Surgery - Zulkifli; Agustina Br Haloho; Legiran; Pirma I.R.M (Journal of Anesthesiology and Clinical Research, 2021)
Introduction: Pain is a problem often encountered in postoperative patients. Study has shown after a procedure, 80% patients experience acute pain. This postoperative pain will affect patient’s quality of life therefore necessitating quick and proper treatment. Tissue trauma during surgery will have influence on body system, including endocrine. One of endocrine system response is cortisol secretion. Cortisol levels may be attenuated by bupivacaine and oxycodone. The aim of this study was to determine the efficacy of bupivacaine0,125% and oxycodone 5 mg on pain perception measured by cortisol in patients undergoing orthopedic surgery of the lower limb. Methods: A randomized clinical trial, double-blind study was performed at Mohammad Hoesin General Hospital in Palembang, South Sumatra, from November to May 2021. There were forty samples and divided into two groups (bupivacaine 0,125% and oxycodone 5 mg). Groups were divided by block randomization by computerized random number generator. Blinding were done by making analgesic has the same packages to prevent knowledge of which intervention is being done. Data were analyzed using independent t-test, ANOVA, Mann-Whitney and Chi Square with SPSS version 22.0. Results: There were no statistically significant differences between the two groups on age, gender, body mass index and duration of surgery. In bupivacaine group, cortisol level decreased from 12.94±6.99 µg/dl to 11.32±5.42 µg/dl meanwhile oxycodone group cortisol levels increased from 11.81±8.47 µg/dl to 11.82±7.56 µg/dl. There were no significant difference between two groups relating to cortisol levels. Conclusions: No significant difference was found on administration of bupivacaine 0,125% and oxycodone 5 mg as epidural analgesia on cortisol level in postoperative orthopedic surgery of the lower limb patient.